Project Report on Planning Structural Analysis and Design of Proposed Boys Hostel Bulding - DIPTADEEP DAS LALA. RANJIT KR PRASAD, CHANDAN KUMAR nad SOMYADEEP SARKAR (2006)
INTERNAL GUIDE: M VEERENDRA KUMAR, MVJCE
Keywords: Structural Analysis and Design